Calculation of Cross Section area and Mean Free path for Interaction of Neutrons with Mammalians cell of Chinese hamster cells (V79) - M. Jaber Al-Ta’iiHassan (Al-Qadisiyah Journal of Pure Science, 2018)
This paper focused on finding the cross-section area and mean free path of the irradiated mammalians cell for the Chinese hamster cells (V79). They were computed based on two models namely Linear Quadratic model (LQ) and Repairable Conditionally Repairable model (RCR). The energy influence on the cross-section area and mean free path was studied. The calculated mean free path by LQ model was higher than the value that obtained by RCR model. Furthermore, the mean free path value is reduced with increasing the linear energy transfer for both models. However, the cross-section area showed a different trend with augmenting the linear energy transfer.